(untitled) (Cardiovascular Journal, 2016)
Background: Hyperhomocysteinemia is known as an independent risk factor of atherosclerosis. But the probable role of Hyperhomocysteinemia in Premature Coronary Artery Disease (CAD) is not well studied. The aim of this study was to assess the role of serum homocysteine on angiographically documented CAD in younger and older ischaemic heart disease (IHD) patients. Methods: Total 120 patients with IHD admitted in the Department of Cardiology, Dhaka Medical College Hospital for CAG were selected by purposive sampling method and divided into two groups. 60 patients in Group-I, d 40 years of age (Younger); 60 patients in Group-II, >40 years of age (Older). Homocysteine was measured in all patients and other demographical and clinical data were collected. Homocysteine level was correlated with the presence and severity of CAD. Results: Smoking, positive family history of IHD, dyslipidaemia and hyper homocysteinemia were important risk factors in younger IHD patients. Whereas, hypertension, diabetes mellitus and dyslipidaemia were important cardiovascular risk factors in older age group. Obesity was not an important risk factors as evidenced by mean BMI. Serum homocysteine was not well related to presence of CAD or extent of CAD in older IHD patients. However in younger patients hyperhomocysteinemia was related to both presence and severity of CAD. Conclusion: In younger IHD patients hyperhomocysteinemia is an important cardiovascular risk factor. But in older patients it loses its significance. So serum homocysteine level should be screened routinely in younger IHD patients. Cardiovasc. j. 2016; 8(2): 138-142